2014
DOI: 10.4025/actascianimsci.v36i1.21641
|View full text |Cite
|
Sign up to set email alerts
|

<b>Ingestive behavior of hoggets given different types of supplement on ryegrass pasture</b>

Abstract: ABSTRACT. The ingestive behavior of hoggets was assessed under intermittent grazing method with three days of paddock occupation. These animals remained exclusively on Italian ryegrass (Lolium multiflorum Lam) pasture or on ryegrass pasture and receiving 1.2% of DM in relation to body weight of rice paddy, corn grain or whole rice bran as a supplement during the vegetative, pre-flowering and flowering phenological stages of ryegrass. The experimental design was a randomized split-split plots wherein the types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…Although some studies indicate that supplementation affects the daily number of bites because of the increased nutrient intake via supplementation (Santana et al, 2013;Stivanin et al, 2014), we found no significant differences in this variable between treatments ( Table 2). The movement rate (9.28 and 11.3 steps min -1 ) and the number of stations visited per min (6.99 and 7.33) reported by P. M. Martini et al (2017) and Rodrigues et al (2019) in cattle grazing sorghum were like those of our study.…”
Section: Resultscontrasting
confidence: 75%
“…Although some studies indicate that supplementation affects the daily number of bites because of the increased nutrient intake via supplementation (Santana et al, 2013;Stivanin et al, 2014), we found no significant differences in this variable between treatments ( Table 2). The movement rate (9.28 and 11.3 steps min -1 ) and the number of stations visited per min (6.99 and 7.33) reported by P. M. Martini et al (2017) and Rodrigues et al (2019) in cattle grazing sorghum were like those of our study.…”
Section: Resultscontrasting
confidence: 75%
“…This in turn promotes an increase in the duration of grazing, which may lead to a restriction of intake and the daily nutrient requirement not being met. Stivanin et al (2014) evaluated the ingestive behavior of hoggets which received different types of supplement on ryegrass pasture, and observed that the daytime grazing is shorter when the hoggets receive supplements, regardless of the type of supplement.…”
Section: Discussionmentioning
confidence: 99%
“…Very long time intervals between grazing can compromise the forage nutrient value, canopy structure, livestock performance, and forage intake. In Italian ryegrass, its phyllochron values have been used as a reference to determine the intervals between grazing by applying the thermal sums concept; examples of reported thermal sums are 312.5 degree-day (DD;CoNFoRTIN et al, 2010;MACHADo et al, 2011), 250 DD (RoSA et al, 2015 and 187.5 DD (STIVANIN et al, 2014;MoTERLE et al, 2017).…”
Section: Plantmentioning
confidence: 99%